Trichome morphology in staurogyne wall. (Acanthaceae) from peninsular Malaysia - Che Amri, Che Nurul Aini; Talip, Noraini; Mohamad, Abdul Latiff; Mohd Johari, Amirul-Aiman; Shahari, Rozilawati; Muhamad Tajudin, Nur Shuhada (The Malayan Nature Journal, 2018)
The morphology of trichome study was carried out in some species of Staurogyne (Acanthaceae) from Peninsular Malaysia. Three taxa studied are S. argentea, S. merguensis and S. setigera var. setigera. The aim of this study is to identify and describe the morphology of trichomes and the methods used are sectioning using sliding microtome, leaf clearing, epidermal peels and observation under both light and scanning electron microscopes. Findings have shown variations in trichome morphology which can be used in species identification. Three forms of trichome were recorded, papillae, glandular and non-glandular. The results showed 12 types of trichome present in Staurogyne. Two types of glandular peltate trichomes, terminal unicellular and terminal multicellular. While for non-glandular trichomes they are simple multicellular and simple unicellular. In conclusions, the findings have shown that trichome morphology has taxonomic significance and can be used in identification of species studied.